Air-liquid interface (ALI) impact on different respiratory cell cultures - Silva, Soraia; Bicker, Joana; Falcão, Amílcar; Fortuna, Ana (European journal of pharmaceutics and biopharmaceutics, 2023)
[Display omitted] The intranasal route has been receiving greater attention from the scientific community not only for systemic drug delivery but also for the treatment of pulmonary and neurological diseases. Along with it, drug transport and permeability studies across the nasal mucosa have exponentially increased. Nevertheless, the translation of data from in vitro cell lines to in vivo studies is not always reliable, due to the difficulty in generating an in vitro model that resembles respiratory human physiology. Among all currently available methodologies, the air–liquid interface (ALI) method is advantageous to promote cell differentiation and optimize the morphological and histological characteristics of airway epithelium cells. Cells grown under ALI conditions, in alternative to submerged conditions, appear to provide relevant input for inhalation and pulmonary toxicology and complement in vivo experiments. Different methodologies and a variety of materials have been used to induce ALI conditions in primary cells and numerous cell lines. Until this day, with only exploratory results, no consensus has been reached regarding the validation of the ALI method, hampering data comparison. The present review describes the most adequate cell models of airway epithelium and how these models are differently affected by ALI conditions. It includes the evaluation of cellular features before and after ALI, and the application of the method in primary cell cultures, commercial 3D primary cells, cell lines and stem-cell derived models. A variety of these models have been recently applied for pharmacological studies against severe acute respiratory syndrome–coronavirus(-2) SARS-CoV(-2), namely primary cultures with alveolar type II epithelium cells and organotypic 3D models. The herein compiled data suggest that ALI conditions must be optimized bearing in mind the type of cells (nasal, bronchial, alveolar), their origin and the objective of the study.